Pengaruh Persepsi Siswa Tentang Full Day School Terhadap Kejenuhan Belajar Pada Mata Pelajaran Akuntansi Berdasarkan Persepsi Siswa Kelas XII Program IPS SMA Negeri 1 Takalar - Reski Resa Putra; M. Ridwan Tikolah; Samsinar Samsinar (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to determine the effect of students' perceptions of full day school on learning boredom in accounting subjects (based on the perceptions of class XII students in the Social Sciences program at SMA Negeri 1 Takalar). The variables in this research are full day school as the independent variable and learning boredom as the dependent variable. The population of this study was all students in class XII IPS 1 and XII IPS 2 at SMA Negeri 1 Takalar. The sampling technique uses a total sampling technique, samples from the population are obtained from the entire population with a sample of 62 students. The data collection techniques used are observation, questionnaires and documentation. The data analysis techniques used are descriptive percentage analysis, instrument testing, and hypothesis testing. Based on the results of the data analysis that has been carried out, the results of descriptive statistical analysis for full day school are 83.72 percent which is classified as very high and student learning saturation is 61.26 percent which is classified as high. From the results of a simple linear regression analysis, full day school Y=1.406 + 0.969X was obtained, which means that for every additional 1 full day school value, learning boredom increased by 0.969. Then the coefficient of determination value was obtained at 0.850 or 85 percent, which means that full day school contributed 85 percent to student learning boredom and the remaining 15 percent was influenced by other factors. Meanwhile, from the results of the t-test analysis, a significant value of 0.000 <0.05 was obtained, which means that full day school has a positive and significant effect on learning boredom, thus the hypothesis is accepted.